Language development and assessment in the preschool period - Conti-Ramsden, Gina; Durkin, K. (Springer New York LLC, 2012)
Most young children make significant progress in learning language during the first 4 years of life. Delays or differences in patterns of language acquisition are sensitive indicators of developmental problems. The dynamic, complex nature of language and the variability in the timing of its acquisition poses a number of challenges for the assessment of young children. This paper summarises the key developmental milestones of language development in the preschool years, providing a backdrop for understanding difficulties with language learning. Children with specific language impairment (SLI) are characterised illustrating the types of language difficulties they exhibit. Genetic evidence for language impairment suggests complex interactions among multiple genes of small effect. There are few consistent neurobiological abnormalities and currently there is no identified neurobiological signature for language difficulties. The assessment of young children’s language skills thus focuses on the evaluation of their performances in comparison to typically developing peers. Assessment of language abilities in preschool children should involve an evaluation of both expressive and receptive skills and should include an evaluation of more than one dimension of language. The use of a single measure of a language component, such as vocabulary, is considered inadequate for determining whether preschool children have typical language or language impairment. Available evidence supports the inclusion of measures of phonological short-term memory in the assessment of the language abilities of preschool children. Further study of genetic, neurobiological and early behavioural correlates of language impairments in preschool children is needed.